Effects of Comorbidities on the Inferior Pedicle Reduction Mammaplasty: A Statistical Analysis. Issue 4 (22nd July 2022) - Friedman, Harold I.; Schlub, Riley; Durkin, Martin; Clark, Emily; Gilstrap, Jarom; McGreevy, Donna
Abstract : Background: Multiple studies have analyzed the impact of comorbidities on breast reduction surgery with mixed results. The purpose of this investigation was to perform a statistical analysis of all complications by a single surgeon, using a single technique for breast reduction. Methods: Records of patients undergoing breast reduction from 1984 to 2019 with an inferior pedicle were reviewed. Comorbidities analyzed included hypertension, diabetes, nicotine use, weight of breast tissue resected, pedicle length, and basal metabolic index. The literature on the effects of comorbidities on outcomes for breast reconstruction was also reviewed. Results: Although increasing body mass index significantly increased the rate of fat necrosis, it did not impact those patients requiring reoperation for this complication. Body mass index greater than 35 kg/m 2, weight of tissue resection greater than 1000 g, and nipple-to–inframammary fold distance greater than 20 cm all increased the odds ratio of having a breast with some fat necrosis. Increasing body mass index increased the risk of wound healing problems (both major and minor), but not for patients requiring reoperation. Body mass index greater than 35 kg/m 2, breast tissue resection greater than 1000 g, and nipple-to–inframammary fold distance greater than 20 cm only minimally increased the odds ratio for a major wound complication. Conclusions: Patients with increased body mass index are at greater risk for fat necrosis and wound healing complications. However, these usually can be managed conservatively in patients undergoing inferior pedicle breast reduction. Patients do not require free nipple grafting. The use of nicotine or the presence of diabetes or hypertension does not impact outcome. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.